Menopause for dummies - Jones, Marcia L. (Wiley Pub., 2007)
Although menopause is a natural and inevitable stage in every woman’s life, its physical, mental, and emotional manifestations can vary greatly from one person to the next. Add to this all of the conflicting “expert” information about the benefits, risks, and side effects to which women are exposed on a daily basis, and it’s easy to see why most find it difficult to make informed choices about how to deal with their menopausal symptoms.